A Study of the Drivers and the Impacts of CSR Activities on Selected Firms in the Indian Leather Industry. - Soleja, Nida (2008)
Corporate social responsibility issues in the developing economies have not gained the attention it warrants and requires, considering that this sector comprises the bulk of the world’s resources supply for multinationals. The purpose of this research is to look into various factors that compel the firms in developing countries to partake in CSR activities and the impact it has on the company’s performance in general. Various drivers are analyzed with the help the conceptual framework, from the ‘stakeholder’s perspective’ and ‘resource-based perspective’ and consequences on the company’s performance from marketing perspective as well as in general were scrutinized. A sample of five firms from the Indian leather industry was selected to achieve the objectives of the research. Data was collected by conducting telephonic interviews with the key decision makers. Case studies were developed with the help of the conceptual framework and an analysis was carried out to reveal the drivers and outcomes of the firms. Results verify that ‘customers’ both directly and indirectly form the major driver for these firms to conduct CSR activities. The study also highlights the enhanced impact on the ‘corporate image’ of the firms. Similar observations were made related to firms ‘productivity and quality’ as well as ‘employee loyalty’.